Music therapy specific outcome measures: an overview. Issue 1 (1st June 2016) - Spiro, Neta; Cripps, Charlotte; Tsiris, Giorgos
Abstract : Background : Outcome assessment in music therapy, in its different guises and forms, has been a core consideration of music therapy work since the early stages of the profession. As a result, music therapists have devised a number of outcome measures that can serve different assessment purposes. Although there are many tools in the public arena, in peer-reviewed or other publications, many do not seem to be used widely in either practice or research. This situation might be connected to limited centralized sources of information about these tools. Objective : The aim of this project is to provide a systematic overview of published outcome measures, and identify trends and gaps in their characteristics. Methods : Following a review of published tools, a database summarizing their characteristics (including the origin, goal and use of each tool) was developed. This database allowed grouping and comparison of the tools. Results and Conclusions : Over 30 tools were identified and compared. By outlining some trends and gaps (e.g. concentration on particular client groups), as well as pointing to a related, newly developed open access resource, with this presentation we hope to raise awareness of existing outcome measures and contribute to the discussion about their potential use in practice.